2012
DOI: 10.1159/000341725
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Team-Based Care Involving Pharmacists to Improve Cardiovascular and Renal Outcomes

Abstract: The number of patients with cardiovascular and kidney disease in the United States continues to grow as the population ages, increasing the demand on the health care system and its providers. Many patients develop chronic conditions in which optimization of care is labor intensive, specifically hypertension, hyperlipidemia, diabetes, heart failure, and chronic kidney disease. Therefore, innovative and collaborative approaches to health care are warranted. Several team-based health care models have evolved and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Collaborative practice agreements are important to integrate pharmacists into the health-care teams in order to maximize their impact. Such agreements expand the role of the pharmacists' role in initiating, modifying, discontinuing, and monitoring drug therapy, ordering or administering laboratory tests, and performing limited physical exams such as checking vital signs and assessing edema [5]. In addition, clinical pharmacy services can provide valuable inputs in identifying drug-related problems and providing suggestions on how they might be avoided [6].…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative practice agreements are important to integrate pharmacists into the health-care teams in order to maximize their impact. Such agreements expand the role of the pharmacists' role in initiating, modifying, discontinuing, and monitoring drug therapy, ordering or administering laboratory tests, and performing limited physical exams such as checking vital signs and assessing edema [5]. In addition, clinical pharmacy services can provide valuable inputs in identifying drug-related problems and providing suggestions on how they might be avoided [6].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Several studies have described the successful integration of a clinical pharmacist within a PCMH setting, yet only a few of those studies evaluated the role of a clinical pharmacist or clinical pharmacy services. [6][7][8][9][10][11][12][13][14][15] Moreover, these studies exclusively examined disease-specific outcomes and did not directly compare outcomes with a standard of care.…”
mentioning
confidence: 99%
“…Our findings suggest that most baseline characteristics and lack of viral response during AVT may no longer be relevant predictive factors when treating patients with SOF-based regimens. A very recent study by Welzel et al [36] also showed that on-treatment HCV RNA quantification is of limited clinical use in patients with advanced liver disease and/or liver transplantation and does not predict SVR12 [36]. Faisal et al [19] have reported similar results in their observational study, which evaluated the efficacy, safety and tolerability of regimens containing sofosbuvir in the treatment of HCV recurrence in all genotypes outside of clinical trials in all Canadian transplant centers [19].…”
Section: Discussionmentioning
confidence: 98%